TECHNOLOGY FOR DESIGNING AN INDIVIDUAL EDUCATIONAL TRAJECTORY OF UNIVERSITY STUDENTS - Ogurechnikova, Natalia; Rumyantsev, Nikolai; Rozhnov, Sergey; Sveshnikova, Olga; Ilinskaya, Irina; Shinkareva, Ludmila; Chauzova, Vera (Revista Inclusiones, 2020)
Lifelong education, aimed at personal and professional development, change of occupation, and mastery of broad-profile qualification in accordance with the supply and demand for highly qualified personnel, is crucial. The continuity of education has to ensure the possibility of a person’s multidimensional progression of a person in the educational space and create optimal conditions for such progression. The continuous education system is currently one of the priorities in the state development policy in Russia. The essence of choosing an individual educational trajectory lies in the student’s decision, which is based on the individual system of values and personal meanings, the general orientation in the spheres of education and labor, highlighting important short- and longterm perspectives as stages and ways of achieving the goal, and the knowledge of one’s own advantages, disadvantages, and unique personal features. The choice of individual educational trajectory is implemented in a subject field that contains a variety of deepened and enriched educational content, types and forms of subject-related material, rational methods of educational activity, forms of control of educational results and individual work, and levels and ways of obtaining an education.